PENERAPAN PEMBELAJARAN SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS PADA MATERI KONDUKTIVITAS THERMAL UNTUK MENINGKATKAN LITERASI STEM SISWA SMA - Harpian, - (2023)
This study aims to analyze the increase in STEM literacy of high school students in the subject of thermal conductivity with the application of STEM learning. The method used in mixed methods. And the design used is exploratory sequential design. This research was conducted in one of the private schools in the city of Bandung. The sample in the study consisted of 31 students of class XI IPA. The research instrument used was a test in the form of multiple choice of 20 questions, an attitude scale in the form of a statement and work assessment observation sheets. The results of the STEM literacy analysis on the knowledge aspect show that it has increased with an n-gain of 0.64 (moderate) and an effect size of 3.10 (strong). Increase in STEM literacy aspects of knowledge in scientific literacy with an n-gain result of 0.71 (high) with an effect size of 1.36 (strong), technology-engineering literacy with an n-gain result of 0.72 (high) and an effect size of 2.14 (strong ) and mathematical literacy with an n-gain result of 0.57 (moderate) and an effect size of 2.12 (strong). The increase in STEM literacy in the attitude aspect experienced a significant increase with an n-gain of 0.41 (moderate) and an effect size of 1.64 (strong). STEM literacy achievement in the skill aspect reaches an average of 88.74. Thus it can be concluded that the application of STEM learning is able to increase STEM literacy in aspects of knowledge, attitudes and skills. This is evidenced by the positive response given by students towards STEM learning.